MODERN PRACTICE OF APPLICATION OF ARTIFICIAL INTELLIGENCE IN THE BANKING FIELD - Кравченко, Вікторія (Modern engineering and innovative technologies, 2023)
The article examines the modern specifics of the formation of a new system of banking services, which is connected with the use of cognitive technologies and artificial intelligence. Artificial intelligence is a significant element of digitalization of